Antibody‐dependent cellular cytotoxicity toward neuroblastoma enhanced by activated invariant natural killer T cells. Issue 3 (9th February 2016) - Mise, Naoko; Takami, Mariko; Suzuki, Akane; Kamata, Toshiko; Harada, Kazuaki; Hishiki, Tomoro; Saito, Takeshi; Terui, Keita; Mitsunaga, Tetsuya; Nakata, Mitsuyuki; Ikeuchi, Takayuki; Nakayama, Toshinori; et al.
Abstract : Anti‐ganglioside GD2 antibodies mainly work through antibody‐dependent cellular cytotoxicity (ADCC) and have demonstrated clinical benefit for children with neuroblastoma. However, high‐risk neuroblastoma still has a high recurrence rate. For further improvement in patient outcomes, ways to maximize the cytotoxic effects of anti‐GD2 therapies with minimal toxicity are required. Activated invariant natural killer T (iNKT) cells enhance both innate and type I acquired anti‐tumor immunity by producing several kinds of cytokines. In this report, we investigated the feasibility of combination therapy using iNKT cells and an anti‐GD2 antibody. Although some of the expanded iNKT cells expressed natural killer (NK) cell markers, including FcγR, iNKT cells were not directly associated with ADCC. When co‐cultured with activated iNKT cells, granzyme A, granzyme B and interferon gamma (IFNγ) production from NK cells were upregulated, and the cytotoxicity of NK cells treated with anti‐GD2 antibodies was increased. Not only cytokines produced by activated iNKT cells, but also NK‐NKT cell contact or NK cell‐dendritic cell contact contributed to the increase in NK cell cytotoxicity and further IFNγ production by iNKT cells and NK cells. In conclusion, iNKT cell‐based immunotherapy could be an appropriate candidate for anti‐GD2 antibody therapy for neuroblastoma. Abstract : We investigated the feasibility of combination therapy using iNKT cells and an anti‐GD2 antibody. Not only cytokines produced by activated iNKT cells, but also NK‐NKT cell contact or NK cell‐dendritic cell contact contributed to the increase in NK cell cytotoxicity and further IFNγ production by iNKT cells and NK cells. iNKT cell‐based immunotherapy could be an appropriate candidate for anti‐GD2 antibody therapy for neuroblastoma.